Utilization of multiple read heads for TMR prediction and correction in bit-patterned media recording - W. Busyatras; C. Warisarn; Y. Okamoto; Y. Nakamura; L. M. M. Myint; P. Supnithi; P. Kovintavewat (My University, 2016)
This paper proposes a utilization of multiple read heads to predict and correct a track mis-registration (TMR) in bit-patterned media recording (BPMR) based on the readback signals. We propose to use the signal energy ratio between the upper and lower tracks from multiple read heads to estimate the TMR level. Then, a pair of two-dimensional (2D) target and its corresponding 2D equalizer associated with the estimated TMR will be chosen to correct the TMR in the data detection process. Numerical results show that the proposed system can achieve a very high accuracy of TMR prediction, thus performing better than the conventional system, especially when TMR is severe.
Keywords: Patterned media; Bit (key); SIGNAL (programming language); Magnetic properties of thin films